"Visual practices and communication" course review - M. M. Brovko, (Ukrainian Cultural Studies, 2018)
(authors-developers: Pavlova O. Yu. ‒ Doctor of Philosophy, Professor of the Department of Ethics, Aesthetics and Cultural Studies of KNU named after Taras Shevchenko and A. M. Tormakhov - Candidate of Philosophy, Assistant of the Department of Ethics, Aesthetics and of cultural studies of Taras Shevchenko Kyiv National University)